2023
DOI: 10.55700/oahsj.v4i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Audiovisual Animation Education as an Effort to Increase Knowledge To Prevent the Risk of Falling Patients in Hospital

Abstract: Background: The risk of falling is one aspect that needs to be studied in patient safety, especially for patients who have a risk of falling due to weakness or the effects of therapy. It can cause injury, increasing the patient’s long of stay, and patient’s treatment fees. The other effects of this are physical injury including scratch, torn, bruised even it can cause fracture, bleeding and head injury. The purpose of this study was to determine the effectiveness of providing audiovisual animation education as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This impact is an increase in the number of re-admissions and in the end patients will bear the costs of in-patient treatment at the hospital. The condition of patient recurrence or patient re-admission is certainly very detrimental to the patient, their family and also the hospital (Rusmawati et al, 2023).…”
Section: The Effectiveness Of Discharge Planning Implementation Of Po...mentioning
confidence: 99%
See 2 more Smart Citations
“…This impact is an increase in the number of re-admissions and in the end patients will bear the costs of in-patient treatment at the hospital. The condition of patient recurrence or patient re-admission is certainly very detrimental to the patient, their family and also the hospital (Rusmawati et al, 2023).…”
Section: The Effectiveness Of Discharge Planning Implementation Of Po...mentioning
confidence: 99%
“…Implementation of discharge planning that is not effective will result in no continuity of care when the patient is at home. This condition can cause the patient's condition to worsen so that the patient returns to the hospital with the same disease or the emergence of more serious disease complications (Rusmawati et al, 2023). Patients with heart failure who are often in and out of the hospital and receive long-term heart failure treatment will have an impact on the patient's quality of life (Zaviera (2007) in (Mahanani, 2017) Based on the results of cross-tabulations conducted by researchers, it was found that respondents with good discharge planning ratings were also accompanied by a good quality of life.…”
Section: The Effectiveness Of Discharge Planning Implementation On Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of animation in education spans various disciplines, from biology to computer science, and has been shown to improve student performance and understanding. In the field of biology education, Reference 64 developed an audiovisual animation education program to increase knowledge about the risk of falling in patients in hospitals. The study found that the use of animation significantly improved the students' understanding of the topic, demonstrating the potential of animation as an effective educational tool.…”
Section: Societal Impacts Of Animationmentioning
confidence: 99%